2003
DOI: 10.1186/1471-2474-4-19
|View full text |Cite
|
Sign up to set email alerts
|

Remission of Behcet's disease with anti-tumor necrosis factor monoclonal antibody therapy: a case report

Abstract: Background: Behcet's disease (BD) is a chronic relapsing multisystem inflammatory disorder with mucocutaneous, ocular, articular, vascular, gastrointestinal and central nervous system manifestations. Tumor necrosis factor (TNF)-alpha is believed to play a pivotal role in BD. Therapeutic blockade of the activity of TNF has been successfully given in a short course of therapy with favorable effects in patients with BD refractory to conventional immunosuppressive drugs. We aimed to find out whether a 12-month tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 17 publications
0
22
0
3
Order By: Relevance
“…In a similar manner, infliximab was shown to be effective in reducing the various mucocutaneous manifestations of the disease [Chan and Lee, 2012;Aikawa et al 2011;Kasugai et al 2010;Lestre et al 2009;Olivieri et al 2008;Connolly et al 2005;Takayama et al 2013;Gulli et al 2003]. …”
Section: ]mentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar manner, infliximab was shown to be effective in reducing the various mucocutaneous manifestations of the disease [Chan and Lee, 2012;Aikawa et al 2011;Kasugai et al 2010;Lestre et al 2009;Olivieri et al 2008;Connolly et al 2005;Takayama et al 2013;Gulli et al 2003]. …”
Section: ]mentioning
confidence: 99%
“…In uveoretinitis, a large number of case reports/ series [Munoz-Fernandez et al 2001;Sfikakis et al 2001;Capella and Foster, 2012;Alokaily et al 2010;Olivieri et al 2008;Takamoto et al 2007;Merino et al 2006;Lindstedt et al 2005;Lanthier et al 2005;Wechsler et al 2004;Sayarlioglu et al 2004a;Rosenbaum, 2004;Giansanti et al 2004;Falappone et al 2004;Morris et al 2003;Gulli et al 2003;Triolo et al 2002;Takayama et al 2013], open-label clinical trials Handa et al 2011;Giardina et al 2011;Tanaka et al 2010;Adan et al 2010;Al-Rayes et al 2008;Tognon et al 2007;Niccoli et al 2007;Accorinti et al 2007;Tugal-Tutkun et al 2005;Benitez-del-Castillo et al 2005;Arayssi et al 2005;Sfikakis et al 2004;Ohno et al 2004;Cantini et al 2012;Keino et al 2011], and nonrandomized comparative studies Yamada et al 2010;Markomichelakis et al 2011] showed that intravenous infliximab, as single therapy, is effective in inducing prompt suppression of ocular inflammation, decreasing the frequency of uveitis attacks and allowing gradual tapering of corticosteroids (CS). As would be expected, vision of eyes with permanent lesions due to irreversible retinal damage does not improve.…”
mentioning
confidence: 99%
“…Até o início de 2002, quando se cogitou usar infliximabe no paciente estudado neste caso, haviam sido descritos na literatura apenas 12 casos semelhantes tratados com infliximabe, ainda sem um consenso com relação à dose, ao número e ao intervalo das infusões. Desde 2002 diversos trabalhos têm sido realizados, alguns com número maior de pacientes, mostrando uma tendência à boa resposta com o uso do infliximabe (9)(10)(11)(12)(15)(16)(17)(18)(19)(20) , havendo apenas descrição de três casos com resposta inadequada (13,14) . O maior estudo, realizado na Grécia e publicado em março de 2004, envolveu 25 pacientes com doença de Behçet e uveíte posterior, que receberam infusão única de infliximab 5 mg/ kg, com controle da inflamação ocular já no primeiro dia pós-tratamento em 24 dos 25 pacientes.…”
Section: Discussionunclassified
“…Of note, anti-TNF-a therapy may be useful in refractory severe BD, particularly in cases with ocular [3], central nervous system [4] and gastrointestinal involvement [5]. The use of this family of biological drugs has also been described in patients with recalcitrant mucocutaneous lesions, and the remarkable early and dramatic response has been associated with relatively long-duration remission [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The use of this family of biological drugs has also been described in patients with recalcitrant mucocutaneous lesions, and the remarkable early and dramatic response has been associated with relatively long-duration remission [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%